الشوفان والجلبان واستعمالها منفردين أو مخلوطين لإنتاج العلف - الصغير, خيري (The Libyan Journal of Agriculture, 2023)
An experiment was conducted on the farm of the Faculty of Agriculture in 1970/71 crop year to compare the forage yield from a pure stand of oats at the rate of 50, 75, and 100 kg. of seed/Ha and the forage from vetch at the rate of 25,50 and 75 kg. of seed/Ha and a mixture of oats and vetch at the following seeding rates,The hay vetch,and 30 percentage with respect to green forage was 40 % % for the oats-vetch mixture.for aots, 26 % for The yield of oats increased by increasing the seeding rate from 50 to 75 and 100 kg./Ha. The same is true of vetch when seeding rate was increased from 25 to 50 and 75 kg./Ha. The highest yield of hay from the oats-vetch mixture was obtained from 25 kg. of oats and 75 kg. of vetch mixture, followed by the 50 kg. of oats and 50 kg. of vetch mixture.In comparing the overall average hay yield regardless of the seeding rate, the oats alone gave the lowest yield, the vetch alone gave a higher yield and the oats - vetch mixture’ gave the highest yield.It appears that 100 kg./Ha of oats alone, 50 kg./Ha of vetch alone, and 50 kg. /Ha of oats and vetch in a mixture are reasonable seeding rates under irrigation in most of the Libyan Arab Republic.A second cutting was obtained from the pure stand of oats, and it appeared that seeding rate had an effect on the forage yield.